MINIMAL GENERATORS SYSTEMS FOR GROUPS OF AUTOMATIC PERMUTATIONS - Сикора, Вера (SWorldJournal, 2021)
The problem of construction of the system of generators for group of finitary automatic permutations is investigated. Theorem about construction of irreducible system of generators for finitary metasymmetric group is proved.